Analysis of Off-label Use of Intravenous Immunoglobulin in a Tertiary Health Care Facility: A Record-based Cross-sectional Study - Mitali Ganapati; Snigdha Rani Panigrahy; Abinash Panda; Jayanti Prava Behera (Journal of Clinical and Diagnostic Research)
Introduction: The off-label clinical use of Intravenous Immunoglobulin (IVIG) has increased despite the existence of its approved indications by drug regulatory agencies. IVIG is an expensive drug and its availability is also limited; hence, judicious use of IVIG is highly recommended. Aim: To evaluate the utilisation pattern and cost burden of IVIG in the In-Patient Departments (IPD) of a tertiary healthcare facility. Materials and Methods: This record-based cross-section observational study was carried out in the IPD of MKCG Medical College, Department of Pharmacology, MKCG, MCH, Berhampur, Odisha, India, from September 2022 to September 2023, where a total of 108 patients who were prescribed and received IVIG for any clinical condition were included. Clinical data, like clinico-demographic profile, diagnosis, dosage and duration of IVIG, were collected in a predesigned structured Case Record Form (CRF). The utilisation pattern was compared with the drug regulatory agencies’ United States Food and Drug Administration (USFDA) approved IVIG conditions to determine the proportion of such use. Data were collected, compiled and analysed using MICROSOFT (MS) Excel and Statistical Package for Social Sciences (SPSS) version 25.0. Data were expressed as frequency, percentages, median and interquartile range. Results: The median age of patients who received IVIG was 12 years and Interquartile Range (IQR) was 29 (Q1=3, Q3=32). Majority of the cases receiving IVIG, i.e., 59 (54.6%), were from paediatrics IPD. The proportion of male patients was higher at 57 (52.7%). Guillain-Barré Syndrome (GBS) was the most common off-label indication, accounting for 55 (50.9%), followed by Multisystem Inflammatory Syndrome (MIS-C) in 12 (11.1%) children. In 73 (67.59%) of cases, IVIG was administered for off-label indication, 8 (6.48%) of cases for FDA-approved indication and remaining for others. The highest expenditure was done on diseases with off-label indications, which accounted for 88.63% of total expenditure for IVIG. Conclusion: In the present study, the use of IVIG for off-label indications was higher than for approved indications. National or local drug protocols are needed to prescribe more rational IVIG utilisation and assist physicians to use IVIG for approved or high evidence-based indications.